Equine Rabies in the Southern Region of Piauí State - Schwarz, David Germano Gonçalves; Barreto, Flávia Melo; Branco, Marlon de Araújo Castelo; Marinho, Glenda Lídice de Oliveira Cortez; Farias, Márcia Paula Oliveira; Monteiro, Hatawa Melo de Almeida; Castro, Rivanni Jeniffer Souza; Tolentino, Mikael Leandro Duarte de Lima (Acta Scientiae Veterinariae, 2020)
Background: Rabies is an infectious disease that is important in the "One Health" worldwide with high lethality rate. The etiological agent is a neurotropic virus, genus Lyssavirus, transmitted mainly through the saliva of infected animals. For equines, the bite of hematophagous bats is the main source of infection. Piauí is an important state for equestrian sports and the increase in the number of horses with neurological clinical signs without diagnosis has increased in recent years. In this context, the aim of this study is to report to the scientific community a confirmed case of equine rabies in the Santa Luz county, Southernmost state of Piauí, Brazil. Case: A 3-year-old female non-defined breed horse, was admitted to the Hospital Veterinário da Universidade Federal do Piauí (UFPI/CPCE). The equine had difficulty walking 2 days ago, in the panoramic inspection was restless and disoriented in the paddock. Rectal temperature of 38.2oC, heart rate of 60 bpm, respiratory rate of 40 mpm, congested mucosa and dyspnea were verified. With the progression of the neurological signals, it positioned itself in a lateral decubitus with pedaling movements, hyperesthesia, dysphagia and paralysis of the hindlimbs. The clinical suspicion was rabies and the Agência de Defesa Agropecuária do Piauí (ADAPI) was communicated to euthanize the animal and collect samples for diagnosis in accordance with official standards of the Ministério da Agricultura, Pecuária e Abastecimento (MAPA). At necropsy, there was slight brain hyperemia, with no other significant organ changes. Fragments of the cerebellum, cortex, hippocampus and spinal cord were collected and sent at a temperature of 4oC to perform the Direct Immunofluorescence (DIF) assay. Samples for histopathology were not collected because they do not include assay for confirmatory diagnosis of rabies. The DIF technique with antigen-labeled antibodies were performed in the imprint lamina of these fragments. The fragments were treated according to specific protocol. The results were negative for DIF in the collected equine fragments. For complementary exam, the samples were homogenized, clarified and inoculated intracranial in BALB/C mice, being observed for up to 30 days. The samples were positive after the bioassay. Discussion: Piauí is a state with great equestrian activity that expose the animals to the risks of transmission of infectious diseases. Among these diseases, rabies is important for affecting horses, but also humans (veterinarians and owners). In the present report, the equine showed clinical signs of furious rabies for a short period, rapidly evolving to paralytic form. This clinical aspect must be carefully evaluated by the veterinarian, in order to avoid false clinical suspicions such as tetanus or other non-infectious diseases. The official diagnosis of the rabies is DIF technique, with high sensitive (80-100%). According to the results of the DIF technique, it was possible to confirm the clinical suspicion of rabies in mice previously inoculated with emulsion of fragments of the equine central nervous system (CNS). This fact demonstrates that in negative results for CNS samples from the horse, the bioassay increases the sensitivity of the test and avoids false negative diagnoses. Thus, it was possible to prove that rabies is affecting the equines in the southern region of Piauí state and alerts the breeders and the community to intensify surveillance and control of the hematophagous bats. For the authors, this is the first scientific report of rabies in the region studied.